ANALYSIS CHARACTERISTIC DEEP WATER RESERVOIR IN DARAM â WARIMPI FORMATION, BINTUNI BASIN, WEST PAPUA INDONESIA - Munazahatin, Ristiya (Techno LPPM, 2015)
Indonesia have a lot of profilic basins which have large oil and gas reserve that produce for supply energy demand in the world. But the trend problem is almost all of mature fields in Weastern Indonesia basin had reaching decline phase peaked oil and gas production since 10 years ago at 1.6 MMbpd. The exploration and exploitation focused to improve the oil recovery (development) and looking for new concepts to optimization of production but its all still havenât served energy demand and high price of oil and gas. Because of that, economic target basin for petroleum industries right now is Eastern Indonesia basin especially in Papua. The potential spread of oil and gas in mature basins, semi-mature basins and frontier basins on the island of Papua, one of mature basin which one already produced is Bintuni Basin. Since the early exploration hydrocarbon in Bintuni Basin focused on deeply target for Kambrium reservoir and not considered much in Paleocene reservoir which one have hydrocarbon potential. The characteristic of Paleocene deep water reservoir is multistory turbidit which one trapped on structural trap and stratigraphic sealing by mudstone. The focused analysis for multistory turbidit reservoir deep water is very important to detail becaused interbedded between sandstone and shalestone will make hydrocarbon got difficult to vertical migration. It could be caused there are permeability barrier or shale break that prevents the hydrocarbon havenât vertical or horizontal migration. The hydrocarbon that couldnât migrate and trapped in reservoir is being bypassed hydrocarbon. One of the alternative technologies to solve those problems and to increasing the recovery factor is making technology called âWindowâ.